Superfine glass microfiber cotton and preparation method thereof
By optimizing raw material ratio, centrifugal disk small hole design and heating method, combined with gas injection technology, the problems of high manual operation difficulty, unstable production and high slag content in the preparation process of ultra-fine glass microfiber cotton in the existing technology are solved, and the preparation efficiency and stability are achieved.
Patent Information
- Application Number
- CN202411751897.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
The existing flame blowing method and centrifugal blowing method have problems such as high manual operation skills requirements, unstable production, high energy consumption, high slag content, many coarse fibers, and insufficient diameter when preparing ultrafine glass microfiber cotton.
The optimized raw material ratio is used to increase the proportion of alkaline oxide components and reduce the viscosity of the glass liquid; the small hole design of the centrifugal disk is optimized to reduce the probability of fiber interference; the electromagnetic induction heating ring is used to replace the traditional spray flame and heat the centrifugal disk; the volume ratio and spray speed of gas to air are controlled to improve the tensile efficiency of glass filaments under the flame.
The preparation efficiency and quality of ultra-fine glass microfiber cotton is improved, and the production of glass slag is reduced, and fibers with finer diameters and lower slag content are obtained, which reduces the difficulty of manual operation and improves production stability.
Smart Images

Figure CN119569348A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ultra-fine glass microfiber cotton preparation, and in particular to an ultra-fine glass microfiber cotton and a preparation method thereof. Background Art
[0002] As an important composite material, glass fiber is widely used in the manufacture of blades for large units. Microfiber glass wool and glass fiber wool, as special materials, are widely used in filter materials, protective materials, separation materials (agglomeration), shielding materials, thermal insulation and sound insulation due to their insulation, heat resistance, flame retardancy and high strength properties.
[0003] The main glass wool fiber-forming processes include flame blowing and centrifugal blowing. In the flame blowing method, the glass balls are melted for a second time, and the glass liquid flows out from the holes in the leak plate and is stretched into primary filaments, which then pass through the fixed screw rod and enter the high-temperature and high-speed flame zone ejected from the combustion nozzle for secondary stretching to form glass microfibers. In the centrifugal blowing method, ultrafine glass fiber wool is prepared by throwing out molten glass liquid at a high temperature through the small holes of a high-speed rotating centrifugal disk, and then directly forming fiber wool through flame blowing.
[0004] However, the production process of the flame blowing method requires manual separation of each filament, which has high requirements for manual operation technology. Once two filaments intersect, glass slag will be produced. There are large fluctuations during production, and the flame mouth is in a straight line shape. The number of primary filaments that can be accommodated is extremely limited, resulting in this preparation method having obvious defects of low output, high energy consumption, and unstable quality, which limits its further application. In the centrifugal blowing method, since the glass liquid is in a high-temperature liquid state in the preparation process, it is very easy to break under the high-temperature and high-speed blowing flame to form slag balls, and the existing centrifugal disk hole design adopts a multi-row repetitive scheme, and the upper and lower rows of holes overlap or intersect. This will cause the primary filaments thrown out from the centrifugal disk to collide and entangle under the extremely high-speed flame blowing during the production of ultra-fine glass fiber wool with a diameter of less than 1.5 microns, resulting in glass slag, coarse fibers, stretching interruption and other problems. It is not easy to prepare glass fibers with a diameter of less than 1.5 microns, uniform thickness and low slag content. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing ultrafine glass microfiber cotton in view of the above problems, which can not only improve the shortcomings of the flame blowing method in terms of high requirements on human operating skills, unstable production and high energy consumption, but also effectively solve the problems of high slag content, many coarse fibers and insufficient diameter when producing ultrafine glass fiber cotton in the centrifugal blowing method.
[0006] The first aspect of the present invention provides a method for preparing ultra-fine glass microfiber cotton, which adopts the following technical scheme: comprising the following steps:
[0007] S1, pretreatment of raw materials, mixing the raw materials in a uniform ratio for standby use, the raw materials include the following components and weight parts: 50-70 parts of high-alkali glass, 6-8 parts of borax, 8-9 parts of quartz sand, 3.5-5 parts of potassium feldspar powder, and 5-7 parts of soda ash;
[0008] S2, preparing glass liquid, heating and melting the raw materials mixed in S1 to obtain glass liquid, cooling after melting, the glass liquid comprises the following components in percentage by weight: SiO2 63-70%, Al2O3 1-3%, CaO3-7%, MgO 2-4%, K2O 0.5-2%, Na2O 16.5-19%, B2O3 4.5-8%, wherein the sum of K2O and Na2O content is between 17-21%;
[0009] S3, preparation of glass filaments, introducing the cooled glass liquid in S2 into a centrifugal disk through an electric heating nozzle, the glass liquid is ejected from the small holes of the centrifugal disk to form glass thin streams, and the glass thin streams are naturally cooled after being ejected to form glass filaments;
[0010] S4, glass microfiber cotton preparation, using gas at a certain temperature through an annular burner to blow and stretch the glass filaments obtained in S3, and after cooling, obtain the finished glass microfiber cotton.
[0011] By adopting the above technical scheme, high-alkali glass contains a large amount of alkaline oxides, and alkaline earth metal oxides serve as the network outer body of the glass. During the melting process of the glass, the melting temperature and viscosity of the glass can be reduced, and the melting and fiber forming of the glass can be promoted; in the glass components, it combines with the silicates in the glass to form silicate hydrates, thereby increasing the chemical stability and water resistance of the glass; in terms of physical and chemical properties, the hardness, strength and heat resistance of the glass can be improved, thereby increasing the service life and safety performance of the glass. Therefore, the raw material ratio is optimized, and the proportion of alkaline oxide components in the formula components is increased to reduce the viscosity of the glass liquid. During the production process, the lower-temperature glass liquid can also maintain sufficient fluidity, so that the glass stream can be thrown out from the small holes of the centrifugal disk. The glass stream is naturally cooled to form glass filaments and then sprayed, so that the glass filaments are reduced in the high-speed blowing flame. Fibers with finer diameters and lower slag content are obtained, and there is no need for manual filament separation, thereby improving the convenience and efficiency of preparing ultra-fine glass microfiber cotton.
[0012] Preferably, the steps include:
[0013] S1, raw material pretreatment, the raw materials are stirred in a mixer for 2 minutes according to the ratio and mixed evenly for standby use, the raw materials include the following components and weight parts: 50-70 parts of high alkali glass, 6-8 parts of borax, 8-9 parts of quartz sand, 3.5-5 parts of potassium feldspar powder, 5-7 parts of soda ash;
[0014] S2, glass liquid preparation, heating the mixed raw materials in S1 to 1300-1500°C to melt to obtain glass liquid, cooling to 1200-1300°C after melting and maintaining the temperature fluctuation within ±1°C, the glass liquid comprises the following components in mass percentage: SiO2 63-70%, Al2O3 1-3%, CaO 3-7%, MgO 2-4%, K2O0.5-2%, Na2O 16.5-19%, B2O3 4.5-8%, wherein the sum of K2O and Na2O content is between 17-21%;
[0015] S3, preparation of glass filaments, the glass liquid after cooling in S2 passes through an electric heating nozzle with a diameter of 15-25 mm, and the flow rate of the glass liquid is controlled by a thermal imager, and introduced into a centrifugal disk, the centrifugal disk is electromagnetically heated, the temperature of the centrifugal disk is 750-850° C., the glass liquid is sprayed out from the small holes of the centrifugal disk to form glass thin streams, and the glass thin streams are naturally cooled after being sprayed out to form glass filaments;
[0016] S4, glass microfiber cotton preparation, using gas at a certain temperature through an annular burner to blow and stretch the glass filaments obtained in S3, and after cooling, obtain the finished glass microfiber cotton.
[0017] Preferably, the diameter of the centrifugal disk in S3 is 200-400 mm, and the rotation speed is 2000-4000 r / min.
[0018] Preferably, the small holes are distributed on the side wall of the centrifugal disk, the number of the small holes is 5000-15000, the diameter of the small holes is 0.5-0.8 mm, the small holes are evenly distributed according to the circumference of the centrifugal disk, and a non-perforated spacing of 0.5-2 mm is left between two adjacent small holes. The small holes in each upper and lower row are staggered, and every two upper and lower rows of the small holes are regarded as a group, and a spacing of one row of the small holes is left between each group.
[0019] Preferably, a circle of electromagnetic inductors is coaxially arranged on the outer side of the centrifugal disk, the power of the electromagnetic inductors is 50-100kw, and the distance between the electromagnetic inductors and the outer circle of the centrifugal disk is 50-150mm.
[0020] Preferably, S3, glass filament preparation, the glass liquid after S2 cooling is passed through an electric heating nozzle with a diameter of 15-25mm, and the glass liquid flow is controlled at 50-100kg / h by a thermal imager, and the flow fluctuation is <5kg / h, and finally introduced into a centrifugal disk with a temperature of 750-850℃, the diameter of the centrifugal disk is 200-400mm, and the rotation speed is 2000-4000r / min. The glass liquid is sprayed out from the small holes of the centrifugal disk to form glass thin streams, and the glass thin streams are naturally cooled through a distance of 5-15mm after being sprayed out to form glass filaments.
[0021] By adopting the above technical scheme, the preparation method is optimized and the quality of the finished glass microfiber cotton product is improved. The small holes of the centrifugal disk are designed to be a group of two rows of holes above and below, and a row of holes is left between each group, so that the probability of mutual interference between the fibers thrown out from the centrifugal disk during the preparation process is reduced, thereby reducing the generation of glass slag. In addition, an electromagnetic induction heating ring is used on the outside of the centrifugal disk to replace the traditional process of heating the centrifugal disk with a jet flame, so that the glass fine flow has a cooling space from being thrown out of the centrifugal disk to the jet flame, thereby reducing the breakage of the glass filaments under the high-speed jet flame, and obtaining fibers with finer diameter and lower slag content.
[0022] Preferably, the fuel gas in S4 is a mixture of natural gas and air, and the volume ratio of natural gas to air is 1:(15-20).
[0023] Preferably, the temperature of the fuel gas during injection is 1300-1500° C., and the injection speed is 300-500 m / s.
[0024] Preferably, during the spraying in S4, the nozzle is in a negative pressure wind chamber, and the pressure in the wind chamber is -1.5 kPa-(-3.5 kPa).
[0025] By adopting the above technical scheme, the volume ratio of natural gas to air and the blowing speed are controlled during blowing, and the gas speed is fast, thereby preparing ultrafine centrifugal glass fiber wool with a smaller diameter and a lower slag content.
[0026] A second aspect of the present invention provides an ultra-fine glass microfiber cotton, which is prepared by any of the preparation methods described above.
[0027] In summary, the present application includes at least one of the following beneficial technical effects:
[0028] 1. Optimize the raw material ratio, increase the proportion of alkaline oxide components in the formula, so that the viscosity of the glass liquid is reduced, and the glass liquid can maintain sufficient fluidity at a relatively low temperature during the production process, so that the glass stream can be thrown out from the small holes of the centrifugal disk. The glass stream is naturally cooled to form glass filaments and then sprayed, so that the glass filaments are less likely to break under the high-speed spraying flame, without the need for manual filament separation, thereby improving the convenience and efficiency of preparing ultra-fine glass microfiber cotton.
[0029] 2. The holes of the centrifugal disk are designed to be a group of two rows of holes, with a row of holes spaced apart between each group. This reduces the probability of interference between fibers thrown out of the centrifugal disk during the preparation process, thereby reducing the generation of glass slag. An electromagnetic induction heating ring is used on the outside of the centrifugal disk to replace the traditional process of heating the centrifugal disk with a jet flame, so that the glass flow has a cooling space from the centrifugal disk to the jet flame after being thrown out of the centrifugal disk. This reduces the breakage of glass filaments under the high-speed jet flame, and obtains fibers with a finer diameter and lower slag content.
[0030] 3. During the injection, the volume ratio of natural gas to air and the injection speed are controlled, and the gas speed is fast, thereby preparing ultra-fine centrifugal glass fiber wool with a smaller diameter and lower slag content.
[0031] 4. The manual operation difficulty of producing ultrafine glass microfiber cotton by this method is relatively low, and the diameter of the ultrafine glass microfiber cotton product is between 0.8 and 1.5 μm, and the slag content is ≤0.4%wt. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the arrangement of the small holes of the centrifugal disk in this application;
[0033] Figure 2 It is a schematic diagram of the structure of the electromagnetic heater in this application;
[0034] Figure 3 It is a schematic diagram of the position of the annular burner and the centrifugal disk in this application;
[0035] Figure 4 This is a SEM image of the glass microfiber cotton obtained in Example 2 of the present application.
[0036] Figure numerals: 1, electric heating nozzle; 2, centrifugal disk; 21, small hole; 3, electromagnetic inductor; 4, annular burner. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0038] In the examples of the present application, high-alkali glass, borax, quartz sand, potassium feldspar, and soda ash are all conventional products available on the market; other specific conditions not specified are carried out according to conventional conditions or conditions recommended by the manufacturer, and the reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased on the market.
[0039] 1. Implementation
[0040] Example 1
[0041] A method for preparing ultrafine glass microfiber cotton comprises the following steps:
[0042] S1. Pretreatment of raw materials: stir the raw materials in a blender for 2 minutes according to the proportion and mix them evenly for later use. The raw materials include the following components and weight parts: 70 parts of high-alkali glass, 6 parts of borax, 8 parts of quartz sand, 3.5 parts of potassium feldspar powder, and 5 parts of soda ash.
[0043] S2, glass liquid preparation, the raw materials mixed in S1 are heated to 1300°C and melted to obtain glass liquid, and after melting, the temperature is gradually lowered to 1200°C and the temperature fluctuation is maintained within ±1°C. The glass liquid includes the following components in mass percentage: SiO2 70%, Al2O3 1%, CaO 7%, MgO 4%, K2O 0.5%, Na2O 16.5%, B2O3 4.5%.
[0044] S3, preparation of glass filaments, the glass liquid after cooling down from S2 passes through an electric heating nozzle 1 with a diameter of 25 mm, and the glass liquid flow rate is controlled to be 100 kg / h by a thermal imager, and is introduced into the centrifugal disk 2 of the centrifugal blowing machine. The diameter of the centrifugal disk 2 is 200 mm, and the rotation speed is 2500 r / min.
[0045] Reference Figure 1 The number of small holes 21 on the centrifugal disk 2 is 5000, and the hole diameter is 0.8 mm. The small holes 21 are evenly distributed according to the circumference of the centrifugal disk 2, and a 2 mm non-perforated spacing is left between two adjacent small holes 21. The small holes 21 in each upper and lower row are staggered, and every two upper and lower rows of small holes 21 are regarded as a group, and a spacing of one row of small holes 21 is left between each group.
[0046] Reference Figure 2 The centrifugal disk 2 is electromagnetically heated. A circle of electromagnetic inductors 3 is coaxially arranged on the outer side of the centrifugal disk 2. The electromagnetic inductors 3 are electromagnetic induction heating circles. The power of the electromagnetic inductors 3 is 50kw. The distance between the electromagnetic inductors 3 and the outer circle of the centrifugal disk 2 is 150mm to ensure that the temperature of the centrifugal disk 2 is 750°C. The glass liquid is ejected from the small holes 21 of the centrifugal disk 2 to form glass thin streams. After the glass thin streams are ejected, they are naturally cooled over a distance of 5mm to form glass filaments.
[0047] S4, glass microfiber cotton preparation, refer to Figure 3The glass filaments obtained by S3 are stretched by using gas at a certain temperature through the annular burner 4 of a centrifugal blower, and the finished glass microfiber cotton is obtained after cooling. The gas is a mixture of natural gas and air, and the air-fuel ratio of the gas is 1:20. The gas blowing temperature is 1300°C, the blowing speed is 300m / s, and the gas is in a negative pressure wind chamber during blowing, and the pressure in the wind chamber is -1.5kPa.
[0048] Example 2
[0049] A method for preparing ultrafine glass microfiber cotton comprises the following steps:
[0050] S1. Pretreatment of raw materials: stir the raw materials in a blender for 2 minutes according to the proportion and mix them evenly for later use. The raw materials include the following components and weight parts: 55 parts of high-alkali glass, 7 parts of borax, 9 parts of quartz sand, 4 parts of potassium feldspar powder, and 6 parts of soda ash.
[0051] S2, glass liquid preparation, the raw materials mixed in S1 are heated to 1400°C for melting to obtain glass liquid, and after melting is completed, the temperature is gradually lowered to 1250°C and the temperature fluctuation is maintained within ±1°C. The glass liquid includes the following components in mass percentage: SiO2 66%, Al2O3 2%, CaO 4.5%, MgO 3%, K2O 1.2%, Na2O 17.5%, B2O3 6%.
[0052] S3, glass filament preparation, the glass liquid after cooling down from S2 passes through an electric heating nozzle 1 with a diameter of 15 mm, and the glass liquid flow rate is controlled to be 50 kg / h by a thermal imager, and is introduced into a centrifugal disk 2, the diameter of the centrifugal disk 2 is 400 mm, and the rotation speed is 4000 r / min.
[0053] The number of small holes 21 on the centrifugal disk 2 is 15,000, and the hole diameter is 0.5 mm. The small holes 21 are evenly distributed according to the circumference of the centrifugal disk 2, and a non-perforated spacing of 0.5 mm is left between two adjacent small holes 21. The small holes 21 in each upper and lower row are staggered, and every two rows of small holes 21 in the upper and lower rows are regarded as a group, and a spacing of one row of small holes 21 is left between each group.
[0054] The centrifugal disk 2 is heated by electromagnetic heating. A circle of electromagnetic inductors 3 is coaxially arranged on the outer side of the centrifugal disk 2. The electromagnetic inductors 3 are electromagnetic induction heating circles. The power of the electromagnetic inductors 3 is 100kw. The distance between the electromagnetic inductors 3 and the outer circle of the centrifugal disk 2 is 50mm to ensure that the temperature of the centrifugal disk 2 is 850°C. The glass liquid is ejected from the small holes 21 of the centrifugal disk 2 to form glass thin streams. After being ejected, the glass thin streams are naturally cooled over a distance of 15mm to form glass filaments.
[0055] S4, glass microfiber cotton preparation, using gas at a certain temperature through the annular burner 4 to stretch the glass filaments obtained in S3, and then cooling to obtain the finished glass microfiber cotton. The gas is a mixture of natural gas and air, and the air-fuel ratio of the gas is 1:15. The gas injection temperature is 1400°C, the injection speed is 500m / s, and the gas is in a negative pressure wind chamber during injection, and the pressure in the wind chamber is -2.5kPa.
[0056] Example 3
[0057] A method for preparing ultrafine glass microfiber cotton comprises the following steps:
[0058] S1. Pretreatment of raw materials: stir the raw materials in a blender for 2 minutes according to the proportion and mix them evenly for later use. The raw materials include the following components and weight parts: 50 parts of high-alkali glass, 8 parts of borax, 8 parts of quartz sand, 5 parts of potassium feldspar powder, and 7 parts of soda ash.
[0059] S2. Preparation of molten glass. The mixed raw materials in S1 are heated to 1500° C. and melted to obtain molten glass. After melting, the temperature is gradually lowered to 1300° C. and the temperature fluctuation is maintained within ±1° C. The molten glass includes the following components in mass percentage: SiO2 63%, Al2O3 3%, CaO 3%, MgO 2%, K2O 2%, Na2O 19%, and B2O3 7%.
[0060] S3, glass filament preparation, the glass liquid after cooling down from S2 passes through an electric heating nozzle 1 with a diameter of 20 mm, and the glass liquid flow rate is controlled to be 80 kg / h by a thermal imager, and is introduced into a centrifugal disk 2, the diameter of the centrifugal disk 2 is 300 mm, and the rotation speed is 2000 r / min.
[0061] The number of small holes 21 on the centrifugal disk 2 is 10,000, and the hole diameter is 0.6 mm. The small holes 21 are evenly distributed according to the circumference of the centrifugal disk 2, and a 1 mm non-perforated spacing is left between two adjacent small holes 21. The small holes 21 in each upper and lower row are staggered, and every two upper and lower rows of small holes 21 are regarded as a group, and a spacing of one row of small holes 21 is left between each group.
[0062] The centrifugal disk 2 is heated by electromagnetic heating. A circle of electromagnetic inductors 3 is coaxially arranged on the outer side of the centrifugal disk 2. The electromagnetic inductors 3 are electromagnetic induction heating circles. The power of the electromagnetic inductors 3 is 75kw. The distance between the electromagnetic inductors 3 and the outer circle of the centrifugal disk 2 is 100mm to ensure that the temperature of the centrifugal disk 2 is 800°C. The glass liquid is ejected from the small holes 21 of the centrifugal disk 2 to form glass thin streams. After being ejected, the glass thin streams are naturally cooled over a distance of 10mm to form glass filaments.
[0063] S4, glass microfiber cotton preparation, using gas at a certain temperature through the annular burner 4 to stretch the glass filaments obtained in S3, and then cooling to obtain the finished glass microfiber cotton. The gas is a mixture of natural gas and air, and the air-fuel ratio of the gas is 1:17. The gas injection temperature is 1500°C, the injection speed is 400m / s, and the gas is in a negative pressure wind chamber during injection, and the pressure in the wind chamber is -3.5kPa.
[0064] 2. Comparison
[0065] Comparative Example 1
[0066] A method for preparing glass microfiber cotton comprises the following steps:
[0067] S1. Raw material pretreatment: select 75 parts of high-alkali glass, 5 parts of borax, 5 parts of quartz sand, 3 parts of potassium feldspar powder, and 5 parts of soda ash in sequence, and stir them in a blender for 2 minutes to mix them evenly.
[0068] S2. Preparation of molten glass: The mixed raw materials are heated to 1400° C. to melt to obtain molten glass. The main components and contents of the molten glass are SiO2 68%, Al2O3 1.5%, CaO 7%, MgO 3%, K2O 1%, Na2O 15%, and B2O3 5%.
[0069] S3, preparation of glass liquid filaments: gradually cool the glass liquid in S2 to 1150°C and keep the temperature fluctuation less than ±1°C; control the flow rate at 100kg / h through an electric heating nozzle with a diameter of 30mm, and introduce it into the centrifugal disk of the centrifugal blowing machine. The centrifugal disk has a rotation speed of 3000r / min, a diameter of 400mm, 15000 holes, and a hole diameter of 0.75mm. The centrifugal disk is directly heated by the contacting blowing flame, and the temperature of the centrifugal disk is about 900°C. The glass liquid is ejected into glass liquid filaments through the holes of the centrifugal disk.
[0070] S4, preparation of glass fiber wool: the molten glass filaments obtained in S3 are directly stretched by a flame at 1400° C., an air-fuel ratio of 1:12, and a spray speed of 400 m / s to obtain a finished glass microfiber wool product after cooling.
[0071] 3. Performance Testing Experiment
[0072] The ultrafine glass microfibers prepared in Examples 1-3 and Comparative Example 1 were sampled and the fiber diameters were measured under a scanning electron microscope; the slag content of the samples was tested according to the provisions of JCT 978-2012.
[0073] The average values of its detection indicators are as follows:
[0074] Table 1 Comparison of finished glass microfiber cotton products
[0075] Fiber diameter (micrometer) Slag content (wt%) Embodiment 1 1.5 0.38 Embodiment 2 0.8 0.28 Embodiment 3 1.2 0.32 Comparative Example 2 0.5
[0076] Referring to Table 1, it can be seen that the diameter of the finished glass microfiber cotton obtained by this method is between 0.8-1.5μm, and the slag content is less than 0.38. Compared with the existing preparation process, the finished product has a finer diameter, a lower slag content, and uniform thickness. Example 2 is the best embodiment of this method, and the preparation process of Example 2 is the best preparation process of this method. The finished glass microfiber cotton obtained in Example 2 is scanned by a scanning electron microscope, and the SEM image is as follows: Figure 4 As shown, there is no obvious slag ball and the finished product is relatively uniform in thickness.
[0077] In summary, the present method optimizes the raw material ratio, increases the proportion of alkaline oxide components in the formula ingredients, reduces the viscosity of the glass liquid, and can maintain sufficient fluidity at a relatively low temperature during the production process, thereby allowing the glass stream to be thrown out from the small holes of the centrifugal disk, optimizes the design of the small holes of the centrifugal disk, reduces the probability of mutual interference between the fibers thrown out from the centrifugal disk during the preparation process, thereby reducing the generation of glass slag, and the glass stream has a cooling space from the centrifugal disk to the blowing flame after being thrown out to the blowing flame, thereby reducing the breakage of the glass filaments under the high-speed blowing flame, and controls the natural gas to air volume ratio and the blowing speed during the blowing, and the gas speed is fast, thereby preparing ultrafine centrifugal glass fiber cotton with a small diameter and a low slag content, and the process has a high degree of mechanization, and no manual filament separation is required, which greatly reduces the difficulty of manual operation and improves production stability.
[0078] Therefore, the use of this method to prepare ultrafine glass microfiber cotton can not only improve the shortcomings of the flame blowing method in terms of high requirements for human operating skills and unstable production, but also effectively solve the problems of high slag content, many coarse fibers, and insufficient diameter when producing ultrafine glass fiber cotton in the centrifugal blowing method.
Claims
1. A method for preparing ultra-fine glass microfiber cotton, characterized in that: The following steps are involved: S1, pretreatment of raw materials, mixing the raw materials in a uniform ratio for standby use, the raw materials include the following components and weight parts: 50-70 parts of high-alkali glass, 6-8 parts of borax, 8-9 parts of quartz sand, 3.5-5 parts of potassium feldspar powder, and 5-7 parts of soda ash; S2, preparing glass liquid, heating and melting the raw materials mixed in S1 to obtain glass liquid, cooling after melting, the glass liquid comprises the following components in percentage by weight: SiO2 63-70%, Al2O3 1-3%, CaO3-7%, MgO 2-4%, K2O0.5-2%, Na2O 16.5-19%, B2O3 4.5-8%, wherein the sum of K2O and Na2O content is between 17-21%; S3, preparation of glass filaments, introducing the cooled glass liquid in S2 into a centrifugal disk through an electric heating nozzle, the glass liquid is ejected from the small holes of the centrifugal disk to form glass thin streams, and the glass thin streams are naturally cooled after being ejected to form glass filaments; S4, glass microfiber cotton preparation, using gas at a certain temperature through an annular burner to blow and stretch the glass filaments obtained in S3, and after cooling, obtain the finished glass microfiber cotton.
2. The preparation method according to claim 1, characterized in that: The following steps are involved: S1, raw material pretreatment, the raw materials are stirred in a mixer for 2 minutes according to the ratio and mixed evenly for standby use, the raw materials include the following components and weight parts: 50-70 parts of high alkali glass, 6-8 parts of borax, 8-9 parts of quartz sand, 3.5-5 parts of potassium feldspar powder, 5-7 parts of soda ash; S2, glass liquid preparation, heating the mixed raw materials in S1 to 1300-1500°C to melt to obtain glass liquid, cooling to 1200-1300°C after melting and maintaining the temperature fluctuation within ±1°C, the glass liquid comprises the following components in mass percentage: SiO2 63-70%, Al2O3 1-3%, CaO 3-7%, MgO 2-4%, K2O0.5-2%, Na2O 16.5-19%, B2O34.5-8%, wherein the sum of K2O and Na2O content is between 17-21%; S3, preparation of glass filaments, the glass liquid after cooling in S2 passes through an electric heating nozzle with a diameter of 15-25 mm, and the flow rate of the glass liquid is controlled by a thermal imager, and introduced into a centrifugal disk, the centrifugal disk is electromagnetically heated, the temperature of the centrifugal disk is 750-850° C., the glass liquid is sprayed out from the small holes of the centrifugal disk to form glass thin streams, and the glass thin streams are naturally cooled after being sprayed out to form glass filaments; S4, glass microfiber cotton preparation, using gas at a certain temperature through an annular burner to blow and stretch the glass filaments obtained in S3, and after cooling, obtain the finished glass microfiber cotton.
3. The preparation method according to claim 2, characterized in that: The diameter of the centrifugal disc in S3 is 200-400 mm, and the rotation speed is 2000-4000 r / min.
4. The preparation method according to claim 2, characterized in that: The small holes are distributed on the side wall of the centrifugal disk, the number of the small holes is 5000-15000, the diameter of the small holes is 0.5-0.8 mm, the small holes are evenly distributed according to the circumference of the centrifugal disk, and a non-perforated spacing of 0.5-2 mm is left between two adjacent small holes. The small holes in each upper and lower row are staggered, and every two upper and lower rows of the small holes are regarded as a group, and a spacing of one row of the small holes is left between each group.
5. The preparation method according to claim 2, characterized in that: A circle of electromagnetic inductors is coaxially arranged on the outer side of the centrifugal disk. The power of the electromagnetic inductors is 50-100kw, and the distance between the electromagnetic inductors and the outer circle of the centrifugal disk is 50-150mm.
6. The preparation method according to claim 2, characterized in that: S3, preparation of glass filaments, the glass liquid after cooling down from S2 passes through an electric heating nozzle with a diameter of 15-25mm, and the flow rate of the glass liquid is controlled at 50-100kg / h by a thermal imager, and the flow rate fluctuation is <5kg / h, and finally introduced into a centrifugal disk with a temperature of 750-850℃, the diameter of the centrifugal disk is 200-400mm, and the rotation speed is 2000-4000r / min. The glass liquid is sprayed out from the small holes of the centrifugal disk to form glass thin streams, and the glass thin streams are naturally cooled through a distance of 5-15mm after being sprayed out to form glass filaments.
7. The preparation method according to claim 1, characterized in that: The fuel gas in S4 is a mixture of natural gas and air, and the volume ratio of natural gas to air is 1:(15-20).
8. The preparation method according to claim 7, characterized in that: The temperature of the fuel gas during injection is 1300-1500°C, and the injection speed is 300-500m / s.
9. The preparation method according to claim 8, characterized in that: During the spraying in S4, the nozzle is placed in a negative pressure wind chamber, and the pressure in the wind chamber is -1.5 kPa-(-3.5 kPa).
10. An ultra-fine glass microfiber cotton, characterized in that: The preparation method is described in any one of claims 1 to 9.